Cooperative Control of Multi-Agent Systems : An Optimal and Robust Perspective - Wang, Jianan, 1982-, author 651570; Wang, Chunyan, author 651571; Xin, Ming, 1972-, author 651573; Ding, Zhengtao, author 555549; Shan, Jiayuan, author 651572; ScienceDirect (Online service) 7722 (London : Academic Press, 2020)
Cooperative Control of Multi-Agent Systems: An Optimal and Robust Perspective reports and encourages technology transfer in the field of cooperative control of multi-agent systems. The book deals with UGVs, UAVs, UUVs and spacecraft, and more. It presents an extended exposition of the authors’ recent work on all aspects of multi-agent technology. Modelling and cooperative control of multi-agent systems are topics of great interest, across both academia (research and education) and industry (for real applications and end-users). Graduate students and researchers from a wide spectrum of specialties in electrical, mechanical or aerospace engineering fields will use this book as a key resource.